Customer Knowledge Management in social media: application of the SMARTUR Framework for the proposition of smart solutions - Emerson Cleister Lima Muniz; Gertrudes Aparecida Dandolini; Alexandre Augusto Biz; Alessandro Costa Ribeiro (Investigaciones Turísticas, 2022)
This research demonstrates the application of the Smart Management of the Tourist Experience (SMARTUR) framework in the intelligent management of tourist experiences shared on TripAdvisor, so as to propose smart solutions in the city of Florianópolis (Brazil). The study also presents the main results obtained from applying the framework and its contribution to an intelligent management of tourist experiences and consequently the improvement of these experiences through the creation of smart solutions for this purpose. In addition, the application demonstrates the need to remodel the way Destination Management Organizations manage the tourist destination and how SMARTUR can contribute to this. More specifically, as it reveals how tourism managers can plan, collect, process, and analyze tourist experiences through their specific dimensions and thus identify strategic points in each of these dimensions that guide DMOs in proposing smart solutions which are more in line with tourist demands.